2015
DOI: 10.1074/jbc.m114.604124
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical psbA Gene Encodes a Sentinel D1 Protein to Form a Physiologically Relevant Inactive Photosystem II Complex in Cyanobacteria

Abstract: Background: Unicellular cyanobacteria separate photosynthesis and nitrogen fixation using a day-night cycle. Results: Cyanothece 51142 expresses a D1 protein exclusively in the dark period that assembles nonfunctional photosystem II. Conclusion:The unusual D1 is named sentinel D1 because it prevents photosynthesis from occurring during nitrogen fixation. Significance: Expression of sentinel D1 allows photosynthesis and nitrogen fixation to coexist in the cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“…Murray, () reported rD1 is a non‐functional version due to the absence of key amino acid residues essential for binding the oxygen evolving CaMn 4 O 5 clusters. Wegener and colleagues () also suggested that in Cyanothece this protein is incorporated into PSII complexes to eliminate their ability to evolve oxygen. Taking into account a large‐scale disassembly of PSII and the overall decrease in intracellular Chl during this phase, the abundance of PSII complexes containing rD1 was negligible as compared to the level of functional PSII complexes during the light phase.…”
Section: Discussionmentioning
confidence: 99%
“…Murray, () reported rD1 is a non‐functional version due to the absence of key amino acid residues essential for binding the oxygen evolving CaMn 4 O 5 clusters. Wegener and colleagues () also suggested that in Cyanothece this protein is incorporated into PSII complexes to eliminate their ability to evolve oxygen. Taking into account a large‐scale disassembly of PSII and the overall decrease in intracellular Chl during this phase, the abundance of PSII complexes containing rD1 was negligible as compared to the level of functional PSII complexes during the light phase.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of D1 can be distinguished phylogenetically (Cardona, Murray, & Rutherford, 2015) and their evolution is schematized in Figure 1c. The early evolving forms, referred to as atypical D1 forms (G0, G1, G2 in Figure 1), are characterized by the absence of some, but not all, of the ligands to the Mn 4 CaO 5 cluster and have been recently found to be involved in the synthesis of chlorophyll f, which supports oxygenic photosynthesis using low energy far-red light (Ho, Shen, Canniffe, Zhao, & Bryant, 2016;Nurnberg et al, 2018); or the inactivation of PSII when anaerobic processes are being carried out (Murray, 2012;Wegener, Nagarajan, & Pakrasi, 2015). The late evolving forms, referred to as the standard D1 forms, are characterized by a complete set of ligands to the Mn 4 CaO 5 cluster and are the main D1 used for water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…1), are characterized by the absence of some, but not all of the ligands to the Mn 4 CaO 5 cluster and have been recently found to be involved in the synthesis of chlorophyll f, which supports oxygenic photosynthesis using low energy far-red light (M. Y. Ho et al, 2016); or the inactivation of PSII when anaerobic process are being carried out such as nitrogen fixation (Murray, 2012;Wegener et al, 2015). The late evolving forms, referred to as the standard D1 forms, are characterized by a complete set of ligands to the Mn 4 CaO 5 cluster and are the main D1 used for water oxidation.…”
Section: Introductionmentioning
confidence: 99%